Spatio-Temporal Analysis of Physico-Chemical Characteristics of Hab River Water, Baluchistan, Pakistan - Rakhshanda Sadaf; S. Jamil Hasan Kazmi; Sofia Khalique Alvi (Journal of Basic & Applied Sciences, 2014)
This study reveals the water quality of Hab River which is the primary source of water supply for Hab City of Baluchistan Province, Pakistan and is also one of the major sources providing water to the mega city of Karachi. The quality of Hab River water is continuously declining owing to the accumulation of industrial effluents of Hab Trading Estate (HTE) and other domestic and agricultural waste. Altogether, 17 samples of water were collected from the study area in pre monsoon and post monsoon seasons and the Physico-chemical parameters like PH, TDS, Turbidity, Salinity, Ca, Mg, Na, K, Cl and SO4 were evaluated. Spatial analysis of PH, TDS, Salinity and Turbidity has also been carried out by conducting interpolation technique in GIS. This analysis spatially explains the differences in different parameters in pre and post-monsoon period. According to Quantitative Indicator (QI), most of the water bodies have crossed the maximum threshold limits defined by WHO guidelines and have entered in to impaired water category.